(untitled) (The Insight, 2025)
Background: Diabetes during pregnancy, both gestational and pre-existing, is an increasing concern in South Asia, linked to higher risks of preeclampsia, cesarean delivery, macrosomia, and neonatal hypoglycemia. This study compared maternal and neonatal outcomes between diabetic and non-diabetic pregnancies in a tertiary hospital. Methods & Materials: This comparative cross-sectional study was carried out in the Department of Gynecology and Obstetrics, Gazi Medical College Hospital, Khulna, Bangladesh, from January to December 2024. A total of 320 pregnant women (160 with diabetes and 160 without) were enrolled to compare maternal and neonatal outcomes. Participants were ≥28 weeks gestation with singleton pregnancies. Data on demographics, antenatal complications, delivery, and neonatal outcomes were collected using a structured questionnaire. Gestational diabetes was diagnosed per IADPSG/WHO 2013 criteria, and analyses were performed using SPSS v26.0. Results: Among 320 pregnant women, most diabetics had gestational diabetes diagnosed at 26 weeks, with 70% achieving good glycemic control. Diabetic mothers showed higher rates of polyhydramnios, caesarean delivery, macrosomia, and shoulder dystocia. Their infants had greater birthweight, more hypoglycaemia, NICU admissions, and longer hospital stays. Adverse maternal (21.3% vs. 11.3%) and neonatal (36.3% vs. 21.3%) outcomes were significantly higher in diabetics. Diabetes, maternal age ≥35 years, and hypertension independently predicted poor outcomes. Conclusion: This study found that diabetes during pregnancy, whether gestational or pre-existing, significantly increases the risk of adverse maternal and neonatal outcomes, including hypertension, cesarean delivery, macrosomia, and neonatal hypoglycemia. Even with reasonable glycemic control, complications remained more common among diabetic mothers than non-diabetic ones.